PENGAJARAN SASTRA MULTIKUTURAL AMERIKA - Setiasari, Winda (Universitas Lancang Kuning, 2008)
The artide discuses the teaching of American Multicultural Literature It indudes the description of writting an effective silabus and conducting some useful, approaches in classroom activity.